Group co-operation, ability and inclusion - Green, Lucy (Music, Informal Learning and the School: A New Classroom Pedagogy, 2008)
I came into the room and there were two boys at the back. One of them had the other in a head-lock. I went up to them and said ‘Why are you doing that?’; and they said, ‘Oh,’ you know, ‘Sorry Sir.’ They took it as a rhetorical question. And they put their heads down: ‘Oh, oh.’ But I said to them ‘No, no I really mean it; I mean why were you doing that – are you bored with the project?’ and they said ‘Oh no, sir, we’re really enjoying it’; and I said ‘Well why were you doing that then?’ and they said, ‘Sir, it’s just that we couldn’t agree on what we’re going to do next.’